A new future for dog breeding - Helle Friis Proschowsky; Maja Louise Arendt; Brenda N Bonnett; Camilla S Bruun; Irena Czycholl; Merete Fredholm; Dan O’Neill; James A Serpell; Peter Sandøe (Animal Welfare)
The modern idea of purebred dogs has come under increasing critical scrutiny over recent decades. In light of this critical focus and other developments in society, some new trends in how companion dogs are bred and acquired have emerged. This means a diminishing influence from traditional kennel clubs with more dogs being sold without a pedigree, stricter legal restrictions on dog breeding, growing popularity of deliberate crosses of established breeds (i.e. so-called designer breeds) and growing hype around the benefits of mixed-breed dogs. We give an overview of these trends and discuss to what extent they will serve to promote dogs that are innately healthy, have good welfare and function well in their various roles in today’s world. We argue that newly invented designer breeds and mixed breeds also have worrying health and behavioural problems, and that the predictability of purebred dogs with respect to body size, basic behaviours, known need for grooming, disorder profiles and other attributes may well offer some benefits for a satisfying human-dog relationship seen from both sides. The optimal future seems to lie in the middle ground, where the future organised dog world (i.e. kennel and breed clubs or their successor organisations) will need to re-open the breed registries, remove wording from breed standards that currently promotes extreme conformation, support selection against disease-predisposing genotypes and phenotypes and refocus dog showing and breeding to promote health and appropriate behaviour.